A Little Help From the Follicles: Understanding the Germinal Center Response to Human Immunodeficiency Virus 1 Infection and Prophylactic Vaccines - Ebony N Gary; Michele A Kutzler (SAGE Publishing, 2017)
Human immunodeficiency virus 1 (HIV-1) is the causative agent of AIDS. There are currently more than 35 million people living with HIV infection worldwide, and more than 2 million new infections occur each year. The global pandemic caused by HIV-1 is the subject of numerous research projects, with the development of a prophylactic vaccine and a therapeutic cure being the ultimate goals. The classic paradigms of vaccinology have proven incapable of producing a viable vaccine due to the complexity of the virus' replication cycle, its genetic diversity, and a lack of understanding of the immune correlates of protection. Here, we briefly discuss recent vaccine approaches and the immune correlates of protection from HIV-1 infection with a focus on the role of the germinal center as a reservoir of replication-competent virus and its role in the development of broadly neutralizing antibodies in response to vaccination.